2004
DOI: 10.1158/0008-5472.can-03-3301
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Autocrine and Paracrine Functions of Granulocyte Colony-Stimulating Factor and Granulocyte-Macrophage Colony-Stimulating Factor in the Progression of Skin Carcinoma Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 48 publications
6
116
0
Order By: Relevance
“…These cells represent an early stage of skin carcinogenesis because they harbor UVB type-specific p53 mutations (Lehman et al, 1993) as well as some chromosomal abnormalities typical for human skin SCCs (Lehman et al, 1993;Boukamp et al, 1997;Popp et al, 2002). While the HaCaT cells remained nontumorigenic through long-term passaging, they became tumorigenic by transduction with the Harvey-ras oncogene, increased temperature or stroma modulating growth factors known to be relevant for tumorigenicity (Boukamp et al, 1990b(Boukamp et al, , 1995(Boukamp et al, , 1997Skobe and Fusenig, 1998;Obermueller et al, 2004). Thus, the intrinsic stable nontumorigenic phenotype, together with the sensitivity for tumorigenic conversion upon distinct changes, make HaCaT cells a highly suitable model to study the role of UVA in skin carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These cells represent an early stage of skin carcinogenesis because they harbor UVB type-specific p53 mutations (Lehman et al, 1993) as well as some chromosomal abnormalities typical for human skin SCCs (Lehman et al, 1993;Boukamp et al, 1997;Popp et al, 2002). While the HaCaT cells remained nontumorigenic through long-term passaging, they became tumorigenic by transduction with the Harvey-ras oncogene, increased temperature or stroma modulating growth factors known to be relevant for tumorigenicity (Boukamp et al, 1990b(Boukamp et al, , 1995(Boukamp et al, , 1997Skobe and Fusenig, 1998;Obermueller et al, 2004). Thus, the intrinsic stable nontumorigenic phenotype, together with the sensitivity for tumorigenic conversion upon distinct changes, make HaCaT cells a highly suitable model to study the role of UVA in skin carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Several other significant GO terms such as ''chemotaxis'' and ''inflammatory response'' or ''chemokine receptor activity'' indicate paracrine effects leading to the recruiting of circulating cells, perhaps neutrophils to the invasion front. Macrophages, 51 neutrophilic granulocytes 52 and mast cells 53 have been shown to exhibit tumor-supporting effects. On the other hand, an inflammatory immune response is a well-known antitumor host reaction.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although CSF2 was originally identified as a hematopoietic growth factor, 23 it has been shown to stimulate tumor growth and migration through an autocrine or paracrine mechanism. [24][25][26] A recent study demonstrates that CSF2 is secreted by senescent fibroblasts. 27 ELISA analysis was employed to measure the concentration of CSF2 in the conditioned media (CM) from irradiated MDA-MB-231-2A cells, and the results showed that CSF2 is release by senescent MDA-MB-231-2A cells (Fig.…”
Section: Csf2 Contributes To Radiation-induced Bystander Effects Via mentioning
confidence: 99%